PERFORMING AND CHARACTERISTIC LYRICS IN UZBEK POETRY - Choriyeva Dilfuza Eshmaxmat qizi (Galaxy International Interdisciplinary Research Journal, 2021)
The article examines the performance and the nature of the lyrics of the Uzbek poetry of the XX century. Some of their works reflect the characteristics of the performing and character lyrics, as well as scientific and literary views.